2021
DOI: 10.1093/europace/euab304
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar ablation of therapy-refractory ventricular arrhythmias: application of a dedicated approach

Abstract: Aims Bipolar radiofrequency ablation (B-RFA) has been reported as a bail-out strategy for the treatment of therapy refractory ventricular arrhythmias (VA). Currently, existing setups have not been standardized for B-RFA, while the impact of conventional B-RFA approaches on lesion formation remains unclear. Methods and results (i) In a multicentre observational study, patients undergoing B-RFA for previously therapy-refractory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…In previous reports, Bi-ABL has been primarily performed for the treatment of ventricular arrhythmias originating from the LV free wall, interventricular septum, LV outflow tract, LV papillary muscles, or His bundle region that were refractory to conventional endocardial and/or epicardial Uni-ABL. 6 , 7 , 8 , 9 , 10 , 11 In the current case, RF energy was delivered between the distal electrodes of 2 irrigated catheters, which were placed in the endocardial and epicardial basal posterior RV. To our knowledge, ours is a rare case in which Bi-ABL has been applied with an endo-epicardial approach to a location in the RV.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous reports, Bi-ABL has been primarily performed for the treatment of ventricular arrhythmias originating from the LV free wall, interventricular septum, LV outflow tract, LV papillary muscles, or His bundle region that were refractory to conventional endocardial and/or epicardial Uni-ABL. 6 , 7 , 8 , 9 , 10 , 11 In the current case, RF energy was delivered between the distal electrodes of 2 irrigated catheters, which were placed in the endocardial and epicardial basal posterior RV. To our knowledge, ours is a rare case in which Bi-ABL has been applied with an endo-epicardial approach to a location in the RV.…”
Section: Discussionmentioning
confidence: 99%
“…Although the methodology of Bi-ABL is well established, severe complications such as cardiac tamponade owing to myocardial injuries by steam pop or atrioventricular block owing to Bi-ABL in the interventricular septum have been reported. 6 , 7 , 8 , 9 , 10 Thus, care is necessary in setting the power level and ablation duration of bipolar RF applications. John et al concluded that ablation duration is the most significant factor in producing durable lesions, whereas the power setting is the most significant factor affecting the incidence of steam pops based on assessment of an ex-vivo Bi-ABL model (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The following impedance indexes were measured 1 ; initial impedance when starting RF application, 2 minimum impedance during ablation, 3 total impedance decline (TID), which was calculated as initial minus minimum impedance during ablation, and 4 %‐TID, which was calculated as percent TID from the initial impedance.…”
Section: Methodsmentioning
confidence: 99%
“…Bipolar (BIP) radiofrequency (RF) catheter ablation, which can create deep lesions, has recently been used for the treatment of arrhythmias originating from inside the thick myocardium 1–3 . Several clinical studies indeed reported that unipolar ablation refractory arrhythmias from deep inside the myocardium were successfully ablated following BIP ablation with excellent acute and long‐term outcomes 4,5 . BIP ablation is useful, but its efficacy seems insufficient for the majority of patients.…”
Section: Introductionmentioning
confidence: 99%